2020
DOI: 10.1111/andr.12925
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CBAVD in azoospermic men carrying pathogenic CFTR mutations ‐ Evaluated in a cohort of 639 non‐vasectomized azoospermic men

Abstract: Background Men with obstructive azoospermia (OA) due to impaired development of the genital tract often carry at least one Cystic Fibrosis Transmembrane Conductance Regulator CFTR mutation. Objective To determine the frequency of Congenital Bilateral Absence of Vas deferens (CBAVD) in men with azoospermia carrying CFTR gene mutations. Materials and methods Non‐vasectomized men with azoospermia referred to our andrological center were consecutively included. All men underwent palpation of the scrotal parts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Several reports include description of the diagnoses of CF during adulthood in patients suffering from CF-like symptoms, such as bronchiectasis or azoospermia [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports include description of the diagnoses of CF during adulthood in patients suffering from CF-like symptoms, such as bronchiectasis or azoospermia [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“… 7 Therefore, some researchers propose that CFTR mutations may affect male fertility through mechanisms other than reproductive tract obstruction. 18 In contrast, other investigators have not found a significant relationship between NOA and CFTR mutations. 19 – 21 We previously found that CFTR is expressed on human sperm and that it plays critical roles in sperm capacitation and fertilizing capability by regulating ion transport.…”
Section: Introductionmentioning
confidence: 90%
“…In a meta-analysis study, 78% of men with CBAVD carried one or two (a severe and a mild or two mild) CFTR variants 7 . CBAVD was found in ~ 44% of a relatively unselected population of azoospermic men with p.Phe508del/ p.Arg117His variants 8 . The variant frequency and hot spots of CFTR gene in Caucasians were demonstrated to be significantly higher than that in individuals of Asian descent.…”
Section: Introductionmentioning
confidence: 99%